2014
DOI: 10.1186/1475-2867-14-17
|View full text |Cite
|
Sign up to set email alerts
|

An eEF1A1 truncation encoded by PTI-1 exerts its oncogenic effect inside the nucleus

Abstract: BackgroundThe oncogene PTI-1 was originally isolated from a prostate cancer cell line by its capability to transform rat fibroblasts. The PTI-1 mRNA has a very eccentric structure as the 5′UTR is similar to prokaryotic 23S rRNA, while the major open reading frame and the 3′UTR corresponds to a part of the mRNA encoding human translation elongation factor eEF1A1. Thus, the largest open reading frame encodes a truncated version of eEF1A1 lacking the first 67 amino acids, while having three unique N-terminal amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…pBLAST of this sequence demonstrated strong sequence homology of this SEP to a 462 amino acid long eukaryotic translation elongation factor 1 from residue 49 to 169. Truncated variants of EEF1A1 have previously been shown to promote 42 or suppress 43 cancer cell growth suggesting that this SEP266 might be an interesting candidate for downstream cell biological studies. The discovery of truncated forms of known proteins, such as EEF1A1, might provide new insight into the biological regulation of these proteins.…”
Section: Resultsmentioning
confidence: 99%
“…pBLAST of this sequence demonstrated strong sequence homology of this SEP to a 462 amino acid long eukaryotic translation elongation factor 1 from residue 49 to 169. Truncated variants of EEF1A1 have previously been shown to promote 42 or suppress 43 cancer cell growth suggesting that this SEP266 might be an interesting candidate for downstream cell biological studies. The discovery of truncated forms of known proteins, such as EEF1A1, might provide new insight into the biological regulation of these proteins.…”
Section: Resultsmentioning
confidence: 99%
“…eEF1A1 is involved in oncogenic transformation. It has been reported that an eEF1A1 truncation encoded by PTI-1 genes has oncogenic roles in transformation of NIH3T3 cells (44). Several differentially expressed gene screening have identified eEF1A1 involved in many types of cancers, such as cervical squamous cell carcinomas, lung squamous-cell carcinoma and breast cancer (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Note that most of the highly reactive, prevalent autoantibodies shown in Table I have some association with cancer-related selfAgs, including BIRC2 (41), CA125 (43), MUC1 (54), stem cell factor (60), S-100 (61), myosin (56), GHRH (26,27), glucagon (29), HGH (31), leptin (33), F3 coagulation factor III (36), EEF1A1 (45), fibronectin (48,49), neurotrophin-3 (58), BCMO1 (63), citrate synthase (66), GST (68), PTGDS (70), laminin (83), and MIF (85). Indeed, we have found that dynamic changes in autoantibody repertoires mark the natural history in mice of variants of a syngeneic, transplantable tumor (112).…”
Section: Discussionmentioning
confidence: 99%